Pengembangan Media Pembelajaran Interaktif untuk Meningkatkan Kreativitas Pembelajaran PKN Siswa Kelas V Sekolah Dasar - Fitriyani Fitriyani; Awalina Barokah; Bulan Kurniati (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research is motivated by the limited teaching materials in elementary schools and the lack of interactive learning media developed. This development research aims to produce a